3+9(-7+4s)=

Simple and best practice solution for 3+9(-7+4s)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+9(-7+4s)= equation:


Simplifying
3 + 9(-7 + 4s) = 0
3 + (-7 * 9 + 4s * 9) = 0
3 + (-63 + 36s) = 0

Combine like terms: 3 + -63 = -60
-60 + 36s = 0

Solving
-60 + 36s = 0

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '60' to each side of the equation.
-60 + 60 + 36s = 0 + 60

Combine like terms: -60 + 60 = 0
0 + 36s = 0 + 60
36s = 0 + 60

Combine like terms: 0 + 60 = 60
36s = 60

Divide each side by '36'.
s = 1.666666667

Simplifying
s = 1.666666667

See similar equations:

| y=2(6) | | -56/-7/8 | | p--2=9 | | -5k+10k=0 | | g(x)=4.9t^2+6t+0.4 | | Log(1/2x) | | -20x+10=6+12x | | -3/4x-2=-8] | | -3(-7+2y)-6= | | -38x+7=159 | | (-9ln(x)-6)/(x^2)=0 | | 10=2x(8)+b | | 12s-s=22 | | -32x=-4 | | 3x=(x*x)-40 | | 18/6d-9=1/6 | | p=2k-2w | | 3X+5X-8=15-X | | Y^2+6Y=-20x-89 | | 9x+17(x+1)=17-4x | | X+7=-4x+2 | | -3n+4=n-3n | | 8.5w=-119 | | (2x-y+5z)(2x-y-5z)= | | 9x+(x+1)=17-4x | | 4w-6=11 | | 7y+5x=148 | | (x-6)/4 | | (k-2)x^2-5x+2=0 | | 5(-3-2m)+7m= | | -35x=35 | | 20=2x+1.5y |

Equations solver categories